أثر السياسات النقدية على ميزان المدفوعات السوداني في الفترة من ۲۰۰۰ حتى ۲۰۱۳م - د.الشاذليعيسىحمدعبدالله (White Nile Journal for Studies and Research, 2015)
This study examines the impact of monetary policies on the Sudanese balance of payments during the period ۲۰۱۳-۲٠٠٠ and assumed that these policies have positive impact on the balance of payments during the study period. and also assumed that these policies have a positive impact on GDP and balance of payments. After analysis of the study results is that monetary policy in the Sudan have led to surpluses in the balance of payments except for three years. and this is not due to such policies alone. but rather refer to the entry of petroleum and gold within the Sudanese exports, and other factors. Finally the study Recommended in coordination between financial and monetary policies. as well as the reform of foreign trade. and stabilizing the exchange rate, and reduce the cost of production, and the treatment of the external debt problem. and achieve a just peace in Sudan and use oil to move the productive sectors and reduce borrowing from the banking system, all in our view lead to further improvement of the balance of payments picture in Sudan.